Rimbaud, Ramuz, Bosco : la forme poétique et ses vertus cathartiques - Michel Arouimi (Carnets)
Some poems of Rimbaud seem to show us the deepest origin of violence, as a sort of cure or exorcism made in (or by) the poem. The same happens in some novels by C.-F. Ramuz, who wanted to « live » Rimbaud, without any imitation. Many novels of Henri Bosco (often associated with Ramuz by french critics) can be read like a synthesis of sacrificial rituals, studied by René Girard. And the act of writing is linked to this enigma.31 janvier 2018